Towards a Lean Approach for Gamifying Education - John, Thomas; Feldotto, Matthias; Hemsen, Paul; Klingsieck, Katrin; Kundisch, Dennis; Langendorf, Mike (Proceedings of the 25th European Conference on Information Systems (ECIS))
Many university students struggle with motivational problems, and gamification has the potential to address these problems. However, using gamification currently is rather tedious and time-consuming for instructors because current approaches to gamification require instructors to engage in the time-consuming preparation of course contents (e.g., for quizzes or mini-games). In reply to this issue, we propose a “lean” approach to gamification, which relies on gamifying learning activities rather than learning contents. The learning activities that are gamified in the lean approach can typically be drawn from existing course syllabi (e.g., attend certain lectures, hand in assignments, read book chapters and articles). Hence, compared to existing approaches, lean gamification substantially lowers the time requirements posed on instructors for gamifying a given course. Drawing on research on limited attention and the present bias, we provide the theoretical foundation for the lean gamification approach. In addition, we present a mobile application that implements lean gamification and outline a mixed-methods study that is currently under way for evaluating whether lean gamification does indeed have the potential to increase students’ motivation. We thereby hope to allow more students and instructors to benefit from the advantages of gamification.

Pick and Place. Englisch für Mechatronik/Lehr-/Arbeitsbuch (3rd edition)

Training and commitment in a German manufacturing company during the post-2008 crisis: a case of internal flexicurity - Schneider, Martin; Flore, Johanna (The International Journal of Human Resource Management)

Signalling to young knowledge workers through architecture? A conjoint analysis - Radermacher, Katharina; Schneider, Martin; Iseke, Anja; Tebbe, Tobias (German Journal of Human Resource Management)

Potenzial der Unternehmensarchitektur im Rahmen des Employer Branding. - Radermacher, Katharina; Schneider, Martin (PERSONALquaterly)

Qualifizieren und binden: Betriebliche Weiterbildung während Kurzarbeit. - Schneider, Martin; Flore, Johanna (PERSONALquaterly)

Signalling to young knowledge workers through architecture? A conjoint analysis - Radermacher, Katharina; Schneider, Martin; Iseke, Anja; Tebbe, Tobias (German Journal of Human Resource Management)

Human resource management and radical innovation: a fuzzy-set QCA of US multinationals in Germany, Switzerland, and the UK - Backes-Gellner, Uschi; Kluike, Marlies; Pull, Kerstin; Schneider, Martin; Teuber, Silvia (Journal of Business Economics)

Cross-cutting organizational and demographic divides and the performance of research and development teams: two wrongs can make a right - Iseke, Anja; Kocks, Birgit; Schneider, Martin; Schulze-Bentrop, Conrad (R&D Management)

Embracing complex causality with the QCA method: An invitation - Schneider, Martin; Eggert, Andreas (Journal of Business Market Management)

A matter of degree: the continuing training gap for women in Europe - Wozny, Caroline; Schneider, Martin (Socio-Economic Review)

„Sekretärin des Vorstandes“ gesucht: Stellenanzeigen und die expressive Funktion des AGG - Bauhoff, Frauke; Schneider, Martin (Industrielle Beziehungen/The German Journal of Industrial Relations)

"Gung Ho": Nationale Kultur und Schlanke Produktion in Ron Howards Spielfilm. - Schneider, Martin (Macht und Employment Relations)

The demand for individual grievance procedures in Germany and Spain: Labour law changes versus business cycle - Frick, Bernd; Ocaña, Miguel Ángel Malo; Martinez, Pilar Garcia; Schneider, Martin (Estudios de economia aplicada)

Schöpferische Zerstörung - Unternehmen haben die Rezession mit teilweise neuen beschäftigungspolitischen Instrumenten bewältigt. - Schneider, Martin; Rütten, Karl-Georg (Personal)

Expatriate compensation packages: what do employees prefer? - Warneke, Doris; Schneider, Martin (Cross Cultural Management: An International Journal)

Which Variety of Measure and Test are Best to Assess the ‘Varieties of Capitalism’Framework? Two Suggestions for Paunescu and Schneider - Allen, Matthew; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Which Variety of Measure and Test are Best to Assess the ‘Varieties of Capitalism’Framework? Two Suggestions for Paunescu and Schneider - Allen, Matthew (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Wettbewerbsfähigkeit und Dynamik institutioneller Standortbedingungen: Ein empirischer Test des „Varieties-of-Capitalism “-Ansatzes - Paunescu, Mihai; Schneider, Martin (Schmollers Jahrbuch: Journal of Applied Social Science Studies/Zeitschrift für Wirtschafts-und Sozialwissenschaften)

Zunehmende Konfliktregulierung durch Arbeitsgerichte? Eine ökonomische Analyse der Häufigkeit von Kündigungsschutzprozessen - Frick, Bernd; Schneider, Martin